From intrabasinal volcanism to far-field tectonics: causes of abrupt shifts in sediment provenance in the Devonian–Carboniferous Drummond Basin, Queensland. Issue 4 (19th May 2019) - Sobczak, K.; Bryan, S. E.; Fielding, C. R.; Corkeron, M.
Abstract: The Drummond Basin of central Queensland preserves a large-volume succession of little studied, predominantly fluviatile, coarse-grained sedimentary rocks of mid-Mississippian age. The stratigraphy of the basin has been subdivided into three sedimentary cycles. The Cycle 1/Cycle 2 boundary records a distinct, but poorly understood change in provenance from a volcanic-dominated succession related to initial basin rifting (Cycle 1) to a quartz-rich, craton-derived succession (Cycle 2). Cycle 3 has been thought to mark a resumption of intrabasinal volcanism and related sedimentation. The purpose of this study was to enhance the understanding of the basin-wide siliciclastic sedimentation of Cycles 2 and 3, and causes for the changes in sediment provenance. This objective was achieved by constraining large-scale spatial and temporal depositional trends and investigating sediment transport pathways into and through the basin. Petrographic, QFL, paleocurrent and conglomerate clast analyses were undertaken. The observations presented here have several implications relevant to understanding the stratigraphy of the Drummond Basin and regional tectonic events at this time. Cycle 3 is revised here primarily to be a continuation of Cycle 2-style basement-derived sedimentation, rather than recording a resumption of volcanism in the area, as per prevailing models. Quartz-rich sedimentation in the Drummond Basin was, therefore, more long-lived than previously envisaged, and once established, was not significantly disrupted by volcanism. Cycle 2 formation thicknesses appear highly variable across the basin. This is unlikely to be a result of pre-existing rift-related topography as suggested in previous models. The thickness variations are more likely related to sediment bypassing and post-depositional deformation in the area. The distinctive coarse-grained, relatively quartz-rich sedimentation of Cycles 2 and 3 is unusual in its volume and extent. The sediment was transported into the basin from its southern/southwestern margin, implying long-distance transport and extrabasinal sediment supply. While the specific source terrain(s) remain unknown, one plausible tectonic driver was far-field influence of the intraplate Alice Springs Orogeny.